The production and comprehension of verbs with alternating transitivity by patients with non-fluent aphasia - Stavrakaki, Stavroula; Alexiadou, Artemis; Kambanaros, Maria; Bostantjopoulou, Sevasti; Katsarou, Zoe (My University, 2011)
Background: Recent studies revealed that aphasic speakers have difficulties with the production of the intransitive (unaccusative) variant of verbs entering transitivity alternations. A key point of the current interpretations of these difficulties concerns the movement operations taking place at surface syntax, namely, the A-movement operation (Bastiaanse & van Zonneveld, 2005; Bastiaanse, 2008; Thompson, 2003). Aim: The present study revisits the issue of processing verbs with alternating transitivity in non-fluent aphasia in Greek, a language with rich morphology and relatively free word order, which lacks A-movement. In addition, in Greek, unaccusative verbs appear with different voice morphology: One class of intransitive variants of alternating verbs bears active morphology, another one non-active morphology and a third one can surface with both. The presence of non-active voice has been argued to correspond to the presence of a voice projection in syntax of these variants, while the variants that bear active morphology are not associated with a voice projection at the level of syntax. This study investigates the ability of non-fluent aphasic speakers to produce and comprehend verbs entering transitivity alterations and explores the role of active vs. non-active morphology and word order in the performance of aphasic speakers. Methods & Procedures: We tested five non-fluent patients and fifteen control participants. We used two tasks supported by pictures: an elicited production task and a comprehension task. The experimental material consisted of fifteen transitive and fifteen unaccusative verbs (marked for active, and/or non-active voice morphology) in sentence contexts. Outcomes & Results: The results indicated that (i) the aphasic speakers performed better on the production and comprehension of transitives than of unaccusatives, (ii) they showed significantly lower performance on the comprehension of unaccusatives with active morphology than on unaccusatives with non-active morphology, and finally (iii) they produced transitive (S)VO structures instead of the unaccusative ones. Conclusion: We suggest, in agreement with other researchers (for example, Schwartz, Linebarger, Saffran, & Pate, 1987) that aphasic individuals overuse a mapping strategy that associates the theta roles of agent and theme with syntactic subject and object respectively, as they produce transitive (S)VO structures, to a large extent, instead of unaccusatives. In addition, as they had difficulties with unaccusative verbs marked for active voice, we suggest that they could not successfully interpret unaccusative verbs with active voice morphology as non-agentive structures.
Keywords: Aphasia; Transitive verbs; Unaccusative verbs; Syntax; Morphology